Index to Philippine periodicals, 2001-2005 disc 2.0 (University Library, UP Diliman, 2007)
The IPP 2001-2005 is a cumulative index to popular and scholarly periodicals published in the Philippines from 2001 to 2005. It consists of bibliographic descriptions of the articles and is searchable by subject and author.